Wages, employment and tenure of temporarily subsidized workers ; does the industry matter? - Gesine Stephan (Institute for the Study of Labor (IZA), 2010)
This paper explores whether wage, employment and tenure outcomes of workers taking up a job subsidized by the German Federal Employment Agency differ by industry. The analysis utilizes administrative data and statistical matching techniques; it covers an observation period of 3.5 years. First, we conduct a within-industry comparison of temporarily subsidized and otherwise similar unsubsidized workers. The findings show for most industries that subsidized workers had similar short-run wages, but fared significantly better in the longer run. Second, we compare labor market outcomes of subsidized workers within each industry with those of similar subsidized workers in other industries. The main result is that cumulated wages of workers would not have differed significantly, if they had been hired in another industry instead. However, we find significant differences in short-term wages, employment and tenure outcomes across industries. Finally, from a fiscal point of view it seems more advantageous to subsidize workers hired in industries that are less subject to demand fluctuations.
Keywords: J31; J38; J58; 330; wage subsidies; industry-specific effects; program evaluation